Modernity could not destroy them: historicizing the African oral artist and the traditional means of communication in Nigeria - Virginia Obioma Eze (Taylor & Francis Group, 2021)
This study examines the identity of the African verbal artist, his communal functions and his role in information dissemination in Nigeria. Before the advent of modern telecommunication systems in Nigeria, the various Nigerian ethnic groups had means of passing on messages/information among them; hence, they were abreast of the issues affecting their corporate existence. With the advent of western civilization came speculations that these African verbal artists and their art would go into oblivion due to the new technological means of communication. However, using a historical approach this research traces the relevance of African traditional mode of communication to entertain, disseminate information, advertise products and services, fulfill psychological, social and economic needs of the communities where they operate. We, therefore, argue that the co-existence of modern and African traditional verbal artists is necessary for effective and comprehensive communicative and service delivery.